Educação na imprensa católica : as representações do jornal A Defesa sobre a formação da juventude (1961-1969) - Santos, Ana Luzia (2006)
This paper approaches the educational patterns that had been spread out by the catholic journal A Defesa , specially those related to youth formation between 1961 and 1969. Through an overview of the releases that had been issued over that period, the aim was to Know the role that the Diocese of Propriá clergy in charge to issue the journal played to the informal formation of the youngsters and their social function. The analysis carried through the concepts of civilization of Norbert Elias. I also make use of index method suggested by the Italian historian Carlo Ginzburg and of Jacques Le Goff notion of document-monument. The research shows that besides the pejorative meaning that had been given to the effervescent youth of that ten years period, the publishers of A Defesa had understood that if a correct education was offered to them, based on the catholic principles, the different youthful groups could have succeeded preventing the dissolution of the familiar institution, thus avoiding the fall of the Christian civilization.